Titanate Nanosheets/Cellulose Composite Showing Improved Crystallinity and Decreased Water Wettability by Gamma-Irradiation - Y. Tariwong; Phieraya Pulphol; Tanagorn Kwamman; Chaowaphat Seriwattanachai; Pongsakorn Kanjanaboos; Phakkhananan Pakawanit; Narong Chanlek; Thitirat Charoonsuk; Hiroaki Onoda; Naratip Vittayakorn; Tosapol Maluangnont (Langmuir, 2025)
layered crystal-a nanosheet precursor. Our work suggests further exploration of nanosheets with diverse structures and compositions as coatings or fillers, which could find applications in γ-irradiation-sterilized barrier films.
Keywords: Advanced Cellulose Research Studies; Polymer Nanocomposite Synthesis and Irradiation; Surface Modification and Superhydrophobicity